Labour Diversity the Gig Economy: A New Approach to Human Resource Management - Asmiatiningsih, Sri (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The gig economy has rapidly changed the traditional employment paradigm and brings unique challenges and opportunities in managing workforce diversity. This study examines the impact of the gig economy on workforce diversity and its implications for human resource management (HRM). Using a systematic literature review (SLR) methodology, we analyse recent academic literature to understand how gig economy dynamics affect diversity in the workplace. Key findings show that while the gig economy encourages greater flexibility and inclusion, it also makes it harder to recruit, develop and retain diverse talent. The study highlights key challenges for organisations such as the integration of diverse gig workers and their engagement and satisfaction. In addition, the study proposes adaptive HRM strategies that can support engagement and optimise the potential of a diverse workforce in gig-based work environments. The recommendations include using technology in distance learning, offering flexible benefits, and fostering a culture of engagement to improve organisational performance and employee well-being.